A novel method for culturing human glottic cells. (17th September 2013) - Bonet, Mireya; Basterra, Jorge; Pérez, Ana; Zapater, Enrique
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis The objective of this basic investigation was to describe a new method of preparing primary monolayer cultures of human glottic cells. To our knowledge, this is the first report of the culturing of healthy human glottic cells. This technique may be of use for other applications in the challenging field of laryngeal diseases. Study Design Individual prospective cohort study. Methods Tissue samples were collected from 15 patients who underwent laryngeal surgery due to chronic laryngitis or larynx carcinoma. An inverted phase microscope was used to study the cultured cells, and immunocytochemistry using a mouse anti‐human cytokeratin 19 monoclonal antibody was performed to identify epithelial cells. The relationship between the culture results and several patient variables was evaluated. Results Cultures were positive in 40% of samples. The total and supracricoid laryngectomy groups had the highest rate of culture positivity (P < .02). Conclusions The current study provides methodological details that will allow other research groups to replicate this model of glottic cell culture. Level of Evidence NA Laryngoscope, 123:E104–E108, 2013